A Generalization of Ćirić Quasicontractions - Erdal Karapınar; Kieu Phuong Chi; Tran Duc Thanh (Abstract and Applied Analysis)
We proved a fixed point theorem for a class of maps that satisfy Ćirić's contractive condition dependent on another function. We presented an example to show that our result is a real generalization.